PEMBUATAN SISTEM PERHITUNGAN HPP DAN PERSEDIAAN BANK SAMPAH INDUK CERIA DI DESA PEGANDEN KECAMATAN MANYAR KABUPATEN GRESIK - Rakhma Devi, Putri Aisyiyah; Rusmiyati, Elyn; Aji, Dhimas Kartika; Sholikah, Aminatus; Rizkiyah, Putri Fira (Jurnal Pengabdian Masyarakat dan Lingkungan, 2022)
Peganden Village is one of the villages in Manyar District, Gresik Regency, East Java Province. The large number of people who live there makes a lot of household waste generated by the community. The Waste Bank is an alternative to manage and organize the collected waste. In its management, the Waste Bank also makes Financial Reports. Therefore, the undergraduate students of the Accounting Study Program of the Regular Blended KKN Group 11 Muhammadiyah University of Gresik in Peganden Village made the HPP system and the Inventory of the Cheerful Main Garbage Bank which aims to make it easier to manage Financial Reports systematically. The socialization was carried out using an understanding method to the participating partners, namely the Treasurer of the Ceria Induk Waste Bank. The success of the implementation of the socialization can be seen from the application of the HPP Calculation System and the Inventory of the Ceria Main Waste Bank by the participating partners.